2017
DOI: 10.3310/hta21100
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to compare the safety, effectiveness and cost-effectiveness of doxycycline (200 mg/day) with that of oral prednisolone (0.5 mg/kg/day) for initial treatment of bullous pemphigoid: the Bullous Pemphigoid Steroids and Tetracyclines (BLISTER) trial

Abstract: BackgroundBullous pemphigoid (BP) is an autoimmune blistering skin disorder with increased morbidity and mortality in the elderly.ObjectivesTo evaluate the effectiveness, safety and cost-effectiveness of a strategy of initiating BP treatment with oral doxycycline or oral prednisolone. We hypothesised that starting treatment with doxycycline gives acceptable short-term blister control while conferring long-term safety advantages over starting treatment with oral prednisolone.DesignPragmatic multicentre two-arme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Sera were stored at −80 °C until used. Inclusion criteria for the BLISTER trial were suspected diagnosis of BP in adults (≥ 18 years) with ≥ three significant blisters appearing on ≥ two body sites within the last week and positive direct or indirect IF microscopy (IgG and/or C3 at the dermoepidermal junction) . Included in the present ancillary study were 69 women and 74 men with a mean age ± SD of 77 (± 11 years; range 40–98).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sera were stored at −80 °C until used. Inclusion criteria for the BLISTER trial were suspected diagnosis of BP in adults (≥ 18 years) with ≥ three significant blisters appearing on ≥ two body sites within the last week and positive direct or indirect IF microscopy (IgG and/or C3 at the dermoepidermal junction) . Included in the present ancillary study were 69 women and 74 men with a mean age ± SD of 77 (± 11 years; range 40–98).…”
Section: Methodsmentioning
confidence: 99%
“…The multicentre prospective BLISTER (Bullous Pemphigoid Steroids and Tetracyclines) trial randomized 253 patients with BP to analyse the safety and effectiveness of initial treatment with doxycycline (200 mg per day) compared with prednisolone (0·5 mg kg −1 per day) . The study found that a strategy of starting patients with BP on doxycycline was noninferior in terms of blister control at 6 weeks and safer in terms of serious related adverse events at 52 weeks when compared with a strategy of starting patients with BP on prednisolone alone .…”
mentioning
confidence: 99%
“…Histological diagnosis should be awaited. For patients with diabetes and in the very old patients, we prefer to omit oral prednisolone and instead use highly potent topical steroids once or twice daily for some weeks and to treat the patients with oral Doxycycline ( 26 , 37 ) or Dapsone ( 27 , 38 , 39 ). BP patients usually experience effect of Doxycycline or Dapsone, respectively, within 3–4 weeks.…”
Section: Treatment Of Bullous Pemphigoidmentioning
confidence: 99%
“…The Bullous Pemphigoid Steroids and Tetracyclines (BLISTER) trial was designed to provide a pragmatic, definitive comparison of starting treatment with the tetracycline doxycycline (200 mg per day) or starting treatment with oral prednisolone (0·5 mg kg −1 per day) . Thus, BLISTER was designed to detect whether an acceptable level of short‐term blister control could be achieved with a strategy of starting treatment with doxycycline (noninferiority), while providing increased long‐term safety when compared with prednisolone.…”
mentioning
confidence: 99%